On Tuza's conjecture for graphs with treewidth at most 6 - Botler, Fábio; Fernandes, Cristina G.; Gutiérrez, Juan (Anais do Encontro de Teoria da Computação (ETC); 2018: Anais do III Encontro de Teoria da Computação, 2018)
Tuza (1981) conjectured that the size τ(G) of a minimum set of edges that meets every triangle of a graph G is at most twice the size ν(G) of a maximum set of edge-disjoint triangles of G. In this paper we verify this conjecture for graphs with treewidth at most 6.